2015
DOI: 10.1016/j.aap.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile phone use on car-following behaviour of young drivers

Abstract: Multitasking, such as the concurrent use of a mobile phone and operating a motor vehicle, is a significant distraction that impairs driving performance and is becoming a leading cause of motor vehicle crashes. This study investigates the impact of mobile phone conversations on car-following behaviour. The CARRS-Q Advanced Driving Simulator was used to test a group of young Australian drivers aged 18-26 years on a car-following task in three randomised phone conditions: baseline (no phone conversation), hands-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 30 publications
(42 reference statements)
3
70
0
1
Order By: Relevance
“…Saifuzzaman et al (55) found that mobile phone use while driving was a significant distraction, especially in young drivers, that impaired driving performance, thus becoming a leading cause of traffic motor vehicle crashes. For example, drivers were more likely to miss traffic signals (stop signs, traffic lights, etc.)…”
Section: Traffic Accidents Adolescence and Risk Factorsmentioning
confidence: 99%
“…Saifuzzaman et al (55) found that mobile phone use while driving was a significant distraction, especially in young drivers, that impaired driving performance, thus becoming a leading cause of traffic motor vehicle crashes. For example, drivers were more likely to miss traffic signals (stop signs, traffic lights, etc.)…”
Section: Traffic Accidents Adolescence and Risk Factorsmentioning
confidence: 99%
“…The SDLP (cm) was calculated according to the mathematical definition described in Verster and Roth (), larger values indicate poorer lane‐keeping performance with higher risks of lane departure and collisions with other vehicles (McLaughlin, Hankey, & Dingus, ). Recent studies have shown that both parameters were sensitive to reveal poorer performance of a driver engaged in phone conversation when followed a preceding vehicle (He et al., ; Saifuzzaman, Haque, Zheng, & Washington, ).…”
Section: Methodsmentioning
confidence: 99%
“…The speed is faster of the following vehicle, the more sensitive the acceleration/deceleration is. On this basis, Sheu [7], Yu [8], Liu [9], Tang [10,11], Yu [12], Zhu [13], Zheng [14], Saifuzzaman [15], Davoodi [16] calibrated parameters in the basic stimulation-reaction model from different perspectives to optimize the model. The study of these researchers helps the model greatly reflect the characteristic of car-following in actual traffic stream.…”
Section: Introductionmentioning
confidence: 99%